2016
DOI: 10.1186/s12934-016-0514-7
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9 mediated targeted mutagenesis of the fast growing cyanobacterium Synechococcus elongatus UTEX 2973

Abstract: BackgroundAs autotrophic prokaryotes, cyanobacteria are ideal chassis organisms for sustainable production of various useful compounds. The newly characterized cyanobacterium Synechococcus elongatus UTEX 2973 is a promising candidate for serving as a microbial cell factory because of its unusually rapid growth rate. Here, we seek to develop a genetic toolkit that enables extensive genomic engineering of Synechococcus 2973 by implementing a CRISPR/Cas9 editing system. We targeted the nblA gene because of its im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
186
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(194 citation statements)
references
References 36 publications
1
186
0
Order By: Relevance
“…Recently, the CRISPR/Cas9 genome editing system, which enhances the recombination efficiency and accelerates the process for chromosome segregation, was used for efficient genome editing in cyanobacteria (Li et al, 2016; Wendt et al, 2016). …”
Section: Resultsmentioning
confidence: 99%
“…Recently, the CRISPR/Cas9 genome editing system, which enhances the recombination efficiency and accelerates the process for chromosome segregation, was used for efficient genome editing in cyanobacteria (Li et al, 2016; Wendt et al, 2016). …”
Section: Resultsmentioning
confidence: 99%
“…Neutral insertion genome regions in the chromosome and fluorescent reporters have been studied (Ruffing et al, 2016). Moreover, genetic engineering of a Synechococcus strain has been achieved using the CRISPR/Cas9 system, although expression of the gene encoding Cas9 brought about severe growth impairment (Wendt et al, 2016). Nonetheless, efficient gene repression of several genes has been implemented using CRISPRi in Synechocystis sp.…”
Section: Cyanobacteriamentioning
confidence: 99%
“…(Johnson et al 2016). Currently, very few studies reported application of a CRISPR/Cas9 genome editing system in the fastgrowing cyanobacterium S. elongatus UTEX 2973, as a proof of concept for the ability to produce a markerfree deletion mutant to target the nblA gene (Wendt et al 2016).…”
Section: Gene Inactivated Gene Insertedmentioning
confidence: 99%